Pengaruh Literasi AI terhadap Kemampuan Berpikir Kritis Siswa melalui Metakognitif pada Mata Pelajaran Ekonomi di SMA Negeri 36 Jakarta - Andini Tiara Putri (Indo Publishing, 2026)
This study aims to analyze the effect of AI literacy on students' critical thinking skills through metacognition in Economics subjects at SMA Negeri 36 Jakarta. The study employed a quantitative approach with a survey method involving 108 students selected using purposive sampling and saturated sampling techniques. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach through SmartPLS 4. The results indicate that AI literacy has a positive and significant effect on critical thinking skills. AI literacy also has a positive and significant effect on metacognition, and metacognition has a positive and significant effect on critical thinking skills. Furthermore, metacognition significantly mediates the effect of AI literacy on critical thinking skills. The model explains 66.8% of the variance in critical thinking skills and 68.5% of the variance in metacognition. These findings confirm that AI literacy, both directly and indirectly through metacognition, contributes to the development of students' critical thinking skills. This study contributes to the understanding of the role of AI literacy and metacognition in enhancing critical thinking skills in the context of economics education, and provides practical implications for teachers and schools in designing learning strategies that integrate AI literacy and metacognitive development.